Three-dimensional porous thick electrode with gradient porosity and preparation method and application thereof

By constructing a three-dimensional porous thick electrode with a gradient porous structure inside the electrode, the problem of regulating the internal ion transmission channel of the electrode in the prior art is solved, and the battery power density and energy density are improved, as well as the electrode stability are improved.

CN119725362APending Publication Date: 2025-03-28SOUTH CHINA UNIV OF TECH
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411782192.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-05
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

The prior art is difficult to effectively regulate the ion transport channel inside the electrode, resulting in polarization of the battery under high current density and the active material of the electrode cannot be fully utilized.

Method used

A three-dimensional porous thick electrode with gradient porosity is used to construct a gradient porous structure inside the electrode, and the porosity of the electrode is adjusted layer by layer by layer by layer by layer, thereby optimizing the structure and performance of the electrode.

Benefits of technology

The power density and energy density of the battery are improved, the curvature inside the electrode is reduced, the effective diffusion rate of ions is enhanced, the kinetics of the electrochemical reaction process is improved, and the stability of the electrode is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119725362A_ABST
    Figure CN119725362A_ABST
Patent Text Reader

Abstract

The invention discloses a three-dimensional porous thick electrode with gradient porosity and a preparation method and application thereof. The thick electrode takes a current collector as a substrate and is formed by stacking electrode slurry layer by layer. Each layer of structure of the porous thick electrode is internally provided with pores which are uniformly distributed, and the porosity of each layer of electrode structure is different and is arranged in a gradient manner along the direction vertical to the plane of the electrode. According to the three-dimensional porous thick electrode with the gradient porosity, due to the gradient macroporous structure in the three-dimensional porous thick electrode, a larger specific surface area is obtained under the condition of not losing excessive active substance loading capacity, the internal bending degree of the thick electrode is reduced, the effective diffusivity of ions in the reaction process is improved, and the specific surface area is increased. And meanwhile, the porous structure also enables the thick electrode to have better stability in the long-cycle charging and discharging process, so that the rate capability and the cycle performance of the electrode can be improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of energy storage / power batteries and relates to a three-dimensional porous thick electrode with gradient porosity and a preparation method and application thereof. Background Art

[0002] With the rapid development of the field of energy and energy storage devices, consumers are increasingly demanding energy storage / power batteries that have both high energy density and high power density, and electrodes are the key factor in determining the quality of the above-mentioned battery performance. In the pursuit of high specific energy, thick electrode technology for various types of ion batteries has emerged. At present, thick electrodes are mostly prepared by coating, which simply doubles the thickness of the electrode to increase the energy density and capacity of the battery. However, the kinetic process of this planar thick electrode is usually very slow. This is because simply increasing the thickness of the electrode leads to an increase in the curvature of the electrode, which dramatically increases the transmission distance of ions in the electrode. At higher current densities, planar thick electrodes will produce obvious polarization phenomena, and the active materials of the electrode cannot be fully utilized. Therefore, from the perspective of electrode structure optimization, it is necessary to design a three-dimensional low-curvature thick electrode structure to improve the corresponding power performance.

[0003] The manufacturing of traditional three-dimensional electrodes usually involves some complex processes, but the rise of 3D printing technology now provides a simpler and more feasible solution for the manufacture of structured three-dimensional thick electrodes. Among the commonly used 3D printing technologies, direct ink writing (DIW) technology has been widely used in the preparation of various types of thick electrodes for ion batteries due to its advantages such as simple printing process, easy operation and strong material compatibility. However, the use of 3D printing technology only optimizes the three-dimensional structured thick electrodes from the macroscopic structural design, and cannot finely regulate the ion transport channels inside the electrode. During the electrochemical reaction, ions are mainly transported in the pores inside the electrode through the electrolyte, and the effective ion diffusion rate is mainly affected by the electrode porosity and electrode curvature. Preparing a porous structure with controllable porosity inside the electrode to reduce the curvature is an effective way to improve the battery rate performance. At present, it is still necessary to effectively combine 3D printing technology and pore-making process to optimize the thick electrode structure at the macro / micro level.

[0004] Therefore, it is necessary to develop a three-dimensional porous thick electrode with gradient porosity that optimizes the power density of the battery while improving the energy density of the battery. Summary of the invention

[0005] In order to solve the problems existing in the prior art, the present invention provides a three-dimensional porous thick electrode with gradient porosity, which has a gradient porous structure inside, thereby improving the battery energy density while optimizing the battery power density.

[0006] The present invention also provides a method for preparing the three-dimensional porous thick electrode with gradient porosity.

[0007] The present invention also provides the use of the three-dimensional porous thick electrode with gradient porosity in the preparation of ion batteries.

[0008] The first aspect of the present invention provides a three-dimensional porous thick electrode with gradient porosity; the porous thick electrode is formed by stacking electrode slurries layer by layer with a current collector as the substrate, each layer of slurry has a specific width and height, and the electrode thickness and active material loading increase with the increase in the number of slurry stacking layers. Each layer structure of the porous thick electrode has uniformly distributed micron-scale pores, and the porosity of each layer of the electrode structure is different and arranged in a gradient along the direction perpendicular to the electrode plane.

[0009] Furthermore, the shape of each layer of the thick electrode structure is any one of an array linear shape, a plane shape, a grid shape, a ring shape and an interdigital shape; preferably, the shape of each layer of the thick electrode structure is set to be an array linear shape and has the same size.

[0010] Furthermore, the thick electrode has a specific layer structure, the height and width of each layer structure range from 0.2 mm to 0.85 mm, the height and width are the same or different, and the width of the upper layer structure is not greater than the width of the lower layer structure.

[0011] Furthermore, each layer of the thick electrode has uniform internal macropore distribution, consistent porosity and most probable pore size. Preferably, each layer has a partial porosity between 20% and 75%, a most probable pore size range of 0.1 μm to 10 μm, and a total pore volume range of 0.06 ml / g to 0.115 ml / g.

[0012] Furthermore, the porosity of each layer structure of the thick electrode is arranged in a positive gradient or a negative gradient from the current collector side to the separator side, and the porosity of two adjacent layer structures varies in the range of 10%-275%.

[0013] A three-dimensional porous thick electrode with gradient porosity and a preparation method thereof, wherein the gradient porous thick electrode of the present invention is obtained by adding water-soluble salts of different masses as pore-forming agents to multiple portions of oily electrode slurries, forming the slurries by a 3D printer, and removing the pore-forming agents by post-processing. Specifically, the steps are as follows:

[0014] (1) using a water-soluble salt as a pore-forming agent, mixing different amounts of water-soluble salt with an electrode active material, a conductive agent, and a binder in a solvent of N-methylpyrrolidone to prepare different groups of electrode slurries;

[0015] (2) using ink direct writing 3D printing technology to deposit different groups of electrode slurries layer by layer on the current collector and form them after drying;

[0016] (3) The formed electrode is immersed in deionized water to remove the pore-forming agent and then dried again.

[0017] According to some embodiments of the present invention, raw materials for preparing the electrode slurry include: an electrode active material, a pore former, a conductive agent, a binder and a solvent.

[0018] According to some embodiments of the present invention, the electrode slurry is composed of the following raw materials in parts by weight: 70-90 parts of electrode active material, 10-200 parts of pore former, 10-20 parts of conductive agent and 10-20 parts of binder; preferably, the mass of the water-soluble salt in the different groups of electrode slurries is 10-200% of the mass of the electrode active material, preferably 20-100%.

[0019] According to some embodiments of the present invention, the electrode active material is a common ionic battery electrode active material.

[0020] According to some embodiments of the present invention, the electrode active material includes at least one of lithium titanate, lithium manganate, lithium iron phosphate, lithium iron silicate, lithium manganese silicate, lithium nickel cobalt manganese, lithium nickel cobalt oxide, sodium iron phosphate, sodium vanadium phosphate, sodium iron sulfate, sodium nickel iron manganate, Prussian white, and hard carbon.

[0021] According to some embodiments of the present invention, the pore-forming agent includes at least one of sodium chloride, sodium carbonate, sodium bicarbonate, ammonium bicarbonate, ammonium citrate, and sucrose, and the particle size range of the particles is 0.1 μm-10 μm.

[0022] According to some embodiments of the present invention, the conductive agent includes at least one of carbon black, acetylene black, graphene, carbon fiber, and carbon nanotubes.

[0023] According to some embodiments of the present invention, the binder includes at least one of polytetrafluoroethylene, low-pressure polyethylene, polyvinylidene fluoride and polyvinyl alcohol.

[0024] According to some embodiments of the invention, the solvent is N-methylpyrrolidone.

[0025] According to some embodiments of the present invention, the stirring speed of the electrode slurry mixing step is 1500rpm-2500rpm.

[0026] According to some embodiments of the present invention, the stirring time of the electrode slurry mixing step is 20 min-50 min.

[0027] According to some embodiments of the present invention, the stirring speed of the electrode slurry degassing step is 1500rpm-2500rpm.

[0028] According to some embodiments of the present invention, the stirring time of the electrode slurry degassing step is 10 min-30 min.

[0029] According to some embodiments of the present invention, the preparation method of the thick electrode is: using a sheet-like current collector as a substrate, using an ink direct writing 3D printer to print different groups of electrode slurries in an array line layer by layer; the first layer of the thick electrode is first printed on the current collector substrate using a group of electrode slurries, and the second layer of the thick electrode is printed and formed using the first layer as a substrate using another group of electrode slurries with different pore-forming agent contents, and the subsequent printed parts are printed and formed by analogy; after the printed thick electrode is formed, it is dried, and then the thick electrode is immersed in heated deionized water to remove the water-soluble pore-forming agent, and the electrode is dried for a second time after the pore-forming agent is removed.

[0030] During 3D printing, different groups of electrode slurries are used to print layer by layer from the current collector side to the diaphragm side in a positive or negative gradient according to the mass of water-soluble salt. The mass of water-soluble salt of the electrode slurry used in two adjacent layers varies in the range of 50-400%.

[0031] The three-dimensional array linear electrodes are all straight-line electrodes of unlimited length. The specific length of the electrode depends on the diameter of the mold selected when cutting the electrode. The width and height of the linear electrode depend on the printing parameters set during ink direct writing 3D printing and the size of the extrusion needle selected. The spacing of the array linear electrode array depends on the array spacing set during ink direct writing 3D printing.

[0032] According to some embodiments of the present invention, the main body width of the three-dimensional array linear electrode is 0.2 mm-0.85 mm.

[0033] According to some embodiments of the present invention, the interval between the three-dimensional array linear electrodes is 1.5-6.5 times the width of the electrode body.

[0034] According to some embodiments of the present invention, the ink direct writing 3D printing device is provided with a storage barrel, and the above-mentioned electrode slurry is loaded in the storage barrel during printing; preferably, the tail end of the storage barrel is connected to the gas valve output port, and the storage barrel is driven by gas to extrude the slurry; preferably, the front end of the storage barrel is equipped with a printing needle to control the main body width of the above-mentioned array linear thick electrode.

[0035] According to some embodiments of the present invention, the current collector is a foam metal material, including one of foam nickel and foam copper.

[0036] According to some embodiments of the present invention, the thickness of the current collector is 0.1 mm-0.5 mm.

[0037] According to some embodiments of the present invention, the needle caliber for ink direct writing 3D printing is 200 μm-850 μm.

[0038] According to some embodiments of the present invention, the needle lifting height set during the ink direct writing 3D printing is not less than 0.2 mm

[0039] According to some embodiments of the present invention, the printing speed set during the ink direct writing 3D printing is 15mm / s-35mm / s.

[0040] According to some embodiments of the present invention, the gas pressure set during the ink direct writing 3D printing is 20psi-40psi.

[0041] According to some embodiments of the present invention, when the ink direct writing 3D prints a layer, the lifting height from the needle tip to the current collector base is 0.2mm-0.85mm; when the ink direct writing 3D prints a second layer, the lifting height from the needle tip to the top of the first layer is 0.15mm-0.8mm.

[0042] Because the foam metal current collector itself has a porous structure, the electrode slurry of the first layer printed by ink direct writing 3D printing is in closer contact with the foam metal substrate, and the stability of the electrode structure is better. Therefore, the needle lifting height is set to be closer to the caliber of the printing needle to ensure that the width and height of the printed three-dimensional linear electrode meet the needle size; when printing the second layer, the structure of the first layer is used as the base. In order to ensure that the two parts are in close contact to ensure the stability of the electrode structure, the needle lifting height of the second layer is slightly lower, which has a certain compaction effect on the first layer.

[0043] According to some embodiments of the present invention, the thick electrode is placed in a vacuum oven for primary drying after printing, the drying temperature is 60° C.-90° C., and the drying time is 6 h-18 h.

[0044] According to some embodiments of the present invention, after the thick electrode is dried once, the pore former is removed by soaking in deionized water, the heating temperature of the deionized water is 60° C.-90° C., and the soaking time is 7 h-12 h.

[0045] According to some embodiments of the present invention, after the pore-forming agent is removed from the thick electrode, it is placed in a vacuum oven for secondary drying at a drying temperature of 60° C.-90° C. and a drying time of 6 h-18 h.

[0046] The second aspect of the present invention provides a method for preparing the above-mentioned three-dimensional porous thick electrode with gradient porosity, wherein a sheet-like current collector is used as a substrate and an ink direct writing 3D printing device is used to prepare the thick electrode body; the first layer of the thick electrode is first printed on the current collector substrate, and the second layer of the thick electrode is then printed and formed with the first layer as a substrate, and the subsequent printed parts are printed and formed in the same way; after the printed thick electrode is formed, it is dried, and then the thick electrode is immersed in heated deionized water to remove the water-soluble pore-forming agent, and the electrode is dried again after the pore-forming agent is removed.

[0047] A three-dimensional porous thick electrode with gradient porosity for use in positive and negative electrodes of lithium and sodium ion batteries.

[0048] According to at least one embodiment of the present invention, the following beneficial effects are achieved:

[0049] The three-dimensional porous thick electrode with gradient porosity of the present invention improves the electrode thickness and active material loading while increasing the porosity by constructing a porous structure inside the electrode, thereby reducing the curvature inside the electrode, and improving the effective diffusion rate of ions in the electrochemical reaction process to solve the problem of low power density of the thick electrode during rapid charging and discharging at a large current; the three-dimensional porous thick electrode with gradient porosity of the present invention realizes layered regulation of the thick electrode structure, and different porosities are set for electrode parts at different thicknesses according to the ion diffusion process in the electrochemical reaction process. This gradient porous structure can improve the battery rate performance and cycle performance while minimizing the loss of energy density that occurs when the thick electrode is pore-formed.

[0050] The present invention combines the traditional pore-forming process with the ink direct writing 3D printing technology, and uses water-soluble salt particles of different mass fractions as pore-forming templates and adds them to the oily electrode slurry system. Finally, the pore-forming agent is removed by soaking in deionized water to generate a porous structure with different porosities. The pore-forming process is simple, the electrode porosity is controlled by the amount of pore-forming agent, and the pore-forming agent removal conditions are mild, without strict temperature conditions or special gas atmosphere requirements, which is convenient for large-scale production; the pore-forming process is applicable to most commonly used oily electrode slurry systems, does not require binding to specific materials, has a wide range of applications, and the addition of pore-forming agents will not affect the properties of other electrode materials themselves. The three-dimensional porous gradient thick electrode with controllable porosity provided by the present invention gives full play to the layer-by-layer superposition characteristics of the 3D printing process, sets the porosity of different electrode parts in layers according to the electrode thickness, and improves the power density and energy density of the electrode at the same time.

[0051] The present invention provides a three-dimensional porous thick electrode with gradient porosity. By constructing a gradient pore structure inside the thick electrode, the internal porosity of the electrode is effectively improved, the transmission distance of ions in the thick electrode during the electrochemical reaction is shortened, and the rate performance of the thick electrode is significantly enhanced. At the same time, the construction of the porous structure increases the specific surface area of ​​the electrode, allowing the electrolyte to more fully infiltrate the inside of the thick electrode. When the battery is charged and discharged with a large current, the electrolyte stored in the porous structure can promptly replenish the ions quickly consumed by the surrounding active materials, thereby enhancing the kinetics of the electrochemical reaction process. The porous structure inside the thick electrode also effectively reduces the expansion of the electrode volume when ions are embedded and released from the electrode, thereby significantly improving the stability of the thick electrode structure.

[0052] The present invention provides a three-dimensional porous thick electrode with gradient porosity, which combines the template method pore-making process and the ink direct writing 3D printing technology, so that water-soluble salt particles of different mass fractions are added as templates into the electrode slurry, and the gradient porous structure thick electrode is conveniently and quickly prepared by 3D printing technology and simple post-processing. This preparation method is not limited to specific battery materials, and does not require high temperature and high pressure or special gas atmosphere to construct a porous structure. The thick electrode can better grasp the balance between energy density and power density of thick electrode ion batteries by combining macro-level layered printing and micro-level pore-making technology. BRIEF DESCRIPTION OF THE DRAWINGS

[0053] Figure 1 The cross-sectional schematic diagram and cross-sectional SEM image are of a three-dimensional porous thick electrode with gradient porosity prepared in Example 2 of the present invention, wherein 1 and 2 refer to the first and second layer structures of the electrode, the width and height of each layer of the electrode may be the same or different, and the pores between adjacent layers show a gradient change.

[0054] Figure 2 Schematic diagram of the assembly of a lithium-ion half-cell with a three-dimensional porous thick electrode having a gradient porosity prepared in Example 3 of the present invention.

[0055] Figure 3 Rate performance diagrams of the lithium ion half-cell with three-dimensional porous thick electrodes with gradient porosity prepared in Examples 3 and 4 of the present invention and the lithium ion half-cell based on three-dimensional array linear thick electrodes without adding pore-forming agent prepared in Comparative Example 1 at charge and discharge rates of 0.5C, 1C, 2C, 3C, 4C, and 5C.

[0056] Figure 4 Capacity performance diagram of the lithium ion half-cell of the three-dimensional porous thick electrode with gradient porosity prepared in Example 4 of the present invention and the lithium ion half-cell based on the three-dimensional array linear thick electrode without the addition of pore-forming agent prepared in Comparative Example 1 at charge and discharge rates of 0.5C, 1C, 2C, 3C, 4C, and 5C.

[0057] Figure 5 The cycling performance diagrams of the lithium ion half-cell with three-dimensional porous thick electrodes with gradient porosity prepared in Examples 3 and 4 of the present invention and the lithium ion half-cell based on three-dimensional array linear thick electrodes without adding pore-forming agent prepared in Comparative Example 1 at a charge and discharge rate of 0.5C.

[0058] Reference numerals:

[0059] 1-a first layer of a three-dimensional gradient porous thick electrode, 2-a second layer of a three-dimensional gradient porous thick electrode, 3-an upper battery shell, 4-a spring, 5-a gasket, 6-a lithium sheet, 7-a diaphragm, 8-a three-dimensional gradient porous thick electrode sheet, 9-a lower battery shell. DETAILED DESCRIPTION

[0060] The following will be combined with the embodiments to clearly and completely describe the concept of the present invention and the technical effects produced, so as to fully understand the purpose, characteristics and effects of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, other embodiments obtained by those skilled in the art without creative work are all within the scope of protection of the present invention.

[0061] In the embodiment of the present invention, lithium titanate, polyvinylidene fluoride and conductive carbon black are purchased from Shenzhen Kejing Zhida Technology Co., Ltd.

[0062] In the embodiment of the present invention, sodium bicarbonate was purchased from Qiancheng Plastic Raw Materials Co., Ltd.

[0063] The length, width and thickness of the nickel foam in the embodiment of the present invention are 150 mm*100 mm*0.5 mm, and it is purchased from Kunshan Guangjiayuan Electronic Materials Business Department.

[0064] Example 1

[0065] A method for preparing a three-dimensional porous thick electrode with gradient porosity comprises the following steps:

[0066] S1: Slurry preparation:

[0067] Weigh 8g of lithium titanate, 4g of sodium bicarbonate, 1g of conductive carbon black and 1g of polyvinylidene fluoride, and then weigh 15mL of N-methylpyrrolidone and put them into the special material cup of the high-speed mixer. Put the material cup into the high-speed mixer and stir at 2500rpm for 20min to mix the materials in the material cup evenly. Then put the electrode slurry in the material cup into the storage barrel of the 3D printer, put the storage barrel into the high-speed mixer for stirring and degassing, and stir at 3000rpm for 7min to obtain a mixed slurry of a thick electrode layer.

[0068] Weigh 8g of lithium titanate, 8g of sodium bicarbonate, 1g of conductive carbon black and 1g of polyvinylidene fluoride, and then weigh 17mL of N-methylpyrrolidone and put them into the special material cup of the high-speed mixer. Put the material cup into the high-speed mixer and stir at 2500rpm for 20min to mix the materials in the material cup evenly. Then put the electrode slurry in the material cup into the storage barrel of the 3D printer, put the storage barrel into the high-speed mixer for stirring and degassing, and stir at 3000rpm for 7min to obtain the mixed slurry of the thick electrode layer.

[0069] S2: Ink direct writing 3D printing thick electrode body:

[0070] Use 150mm*100mm*0.5mm nickel foam as the current collector of the three-dimensional array linear electrode, install the storage cylinder containing the mixed slurry of one layer prepared in step S1 on the 3D printer, the printing needle diameter of one layer is 400μm, set relevant printing parameters (printing speed 15mm / s, gas pressure 30psi, three-dimensional array linear electrode length 140mm, array line spacing 1.4mm, printing needle lifting height 0.4mm) to complete the printing of one layer of the electrode body.

[0071] The storage cylinder containing the mixed slurry of the second layer prepared in step S1 is installed on the 3D printer. The printing needle diameter of the second layer is 400 μm. The relevant printing parameters are set (printing speed 15 mm / s, gas pressure 30 psi, three-dimensional array linear electrode length 140 mm, array line spacing 1.4 mm, printing needle lifting height 0.75 mm), and the second layer electrode body is printed on the top of the first layer.

[0072] Place the printed thick electrode in a vacuum oven and set the drying temperature to 70°C and the drying time to 12 hours.

[0073] S3: Post-processing of 3D printed thick electrodes:

[0074] The dried and formed thick electrode was completely immersed in deionized water at 80° C. for 7 hours to remove the pore-forming agent.

[0075] After the deionized water soaking step is completed, the thick electrode is placed in the vacuum oven again for drying, and the drying temperature is set to 70° C. and the drying time is set to 12 h.

[0076] In this embodiment, the width of the electrode body of the first layer and the second layer is about 400 μm, and the overall height is about 780 μm. The porosity of the first layer is about 47%, and the porosity of the second layer is about 60%.

[0077] Example 2

[0078] A method for preparing a three-dimensional porous thick electrode with gradient porosity comprises the following steps:

[0079] S1: Slurry preparation:

[0080] Weigh 8g of lithium titanate, 8g of sodium bicarbonate, 1g of conductive carbon black and 1g of polyvinylidene fluoride, and then weigh 15mL of N-methylpyrrolidone and put them into the special material cup of the high-speed mixer. Put the material cup into the high-speed mixer and stir at 2500rpm for 20min to mix the materials in the material cup evenly. Then put the electrode slurry in the material cup into the storage barrel of the 3D printer, put the storage barrel into the high-speed mixer for stirring and degassing, and stir at 3000rpm for 7min to obtain a mixed slurry of a thick electrode layer.

[0081] Weigh 8g of lithium titanate, 4g of sodium bicarbonate, 1g of conductive carbon black and 1g of polyvinylidene fluoride, and then weigh 17mL of N-methylpyrrolidone and put them into the special material cup of the high-speed mixer. Put the material cup into the high-speed mixer and stir at 2500rpm for 20min to mix the materials in the material cup evenly. Then put the electrode slurry in the material cup into the storage barrel of the 3D printer, put the storage barrel into the high-speed mixer for stirring and degassing, and stir at 3000rpm for 7min to obtain the mixed slurry of the thick electrode layer.

[0082] S2: Ink direct writing 3D printing thick electrode body:

[0083] Use 150mm*100mm*0.5mm nickel foam as the current collector of the three-dimensional array linear electrode, install the storage cylinder containing the mixed slurry of one layer prepared in step S1 on the 3D printer, the printing needle diameter of one layer is 400μm, set relevant printing parameters (printing speed 15mm / s, gas pressure 30psi, three-dimensional array linear electrode length 140mm, array line spacing 1.4mm, printing needle lifting height 0.4mm) to complete the printing of one layer of the electrode body.

[0084] The storage cylinder containing the mixed slurry of the second layer prepared in step S1 is installed on the 3D printer. The printing needle diameter of the second layer is 400 μm. The relevant printing parameters are set (printing speed 15 mm / s, gas pressure 30 psi, three-dimensional array electrode length 140 mm, array line spacing 1.4 mm, printing needle lifting height 0.75 mm), and the second layer electrode body is printed on the top of the first layer.

[0085] Place the printed thick electrode in a vacuum oven and set the drying temperature to 70°C and the drying time to 12 hours.

[0086] S3: Post-processing of 3D printed thick electrodes:

[0087] The dried and formed thick electrode was completely immersed in deionized water at 80° C. for 7 hours to remove the pore-forming agent.

[0088] After the deionized water soaking step is completed, the thick electrode is placed in the vacuum oven again for drying, and the drying temperature is set to 70° C. and the drying time is set to 12 h.

[0089] In this embodiment, the width of the electrode body of the first layer and the second layer is about 400 μm, and the overall height is about 780 μm. The porosity of the first layer is about 60%, and the porosity of the second layer is about 47%.

[0090] Example 3

[0091] This embodiment is a lithium-ion half-cell. The positive electrode of the lithium-ion battery of this embodiment adopts the three-dimensional porous thick electrode with gradient porosity prepared in Example 1, and the lithium sheet is used as the negative electrode. When assembling the battery, the three-dimensional porous thick electrode with gradient porosity prepared in Example 1 is directly in contact with the diaphragm, and the base nickel foam is directly in close contact with the battery shell. Figure 2 FIG. 1 is a schematic diagram of the lithium-ion half-cell assembly of this embodiment. Figure 2 As shown, the three-dimensional gradient porous thick electrode sheet 8 is placed on the lower battery shell 9, and the electrolyte directly infiltrates the active material on the three-dimensional gradient porous thick electrode sheet 8. The electrolyte (1 mol / L lithium hexafluorophosphate solution) fills the entire cavity composed of the three-dimensional gradient porous thick electrode sheet 8, the lower battery shell 9 and the diaphragm 7. The lithium sheet 6 is tightly attached to the diaphragm 7, and the gasket 5 and the spring 4 are placed on the upper surface of the lithium sheet 6 from bottom to top. The gasket 5 and the spring 4 are used to adjust the pressure of the battery; the spring 4 is in close contact with the upper battery shell 3 to reduce the contact resistance and ensure good conductivity inside the battery.

[0092] The LAND CT2001A battery testing system was used to test the cycle performance and rate performance of the lithium ion half-cell with the three-dimensional porous thick electrode with gradient porosity prepared in Example 3 (all tests were carried out at room temperature (25° C.) and the voltage range was 1 V to 2.5 V).

[0093] Example 4

[0094] This embodiment is a lithium ion half-cell. The positive electrode of the lithium ion battery of this embodiment adopts the three-dimensional porous thick electrode with gradient porosity prepared in Example 2, and the lithium sheet is used as the negative electrode. The method of assembling the battery refers to that in Example 3.

[0095] The LAND CT2001A battery testing system was used to test the cycle performance and rate performance of the lithium ion half-cell with the three-dimensional porous thick electrode with gradient porosity prepared in Example 4 (all tests were carried out at room temperature (25° C.) and the voltage range was 1 V to 2.5 V).

[0096] Comparative Example 1

[0097] This comparative example is a lithium ion half-cell based on a double-layer three-dimensional array linear electrode without adding a pore-forming agent.

[0098] The preparation method of the double-layer three-dimensional array linear electrode in this comparative example consists of the following steps:

[0099] S1: Slurry preparation:

[0100] Weigh 8g of lithium titanate, 1g of conductive carbon black and 1g of polyvinylidene fluoride, and then weigh 13mL of N-methylpyrrolidone and put them into the special material cup of the high-speed mixer. Put the material cup into the high-speed mixer and stir at 2500rpm for 20min to mix the materials in the material cup evenly. Then put the electrode slurry in the material cup into the storage barrel of the 3D printer, put the storage barrel into the high-speed mixer for stirring and degassing, and stir at 3000rpm for 7min to obtain the mixed slurry of the electrode body.

[0101] S2: Ink direct writing 3D printing thick electrode body:

[0102] Use 150mm*100mm*0.5mm nickel foam as the current collector of the three-dimensional array linear electrode, install the storage cylinder containing the mixed slurry prepared in step S1 on the 3D printer, the printing needle diameter of one layer is 400μm, set relevant printing parameters (printing speed 15mm / s, gas pressure 30psi, three-dimensional array linear electrode length 140mm, array line spacing 1.4mm, printing needle lifting height 0.4mm) to complete the printing of one layer of the electrode body.

[0103] The printing needle diameter of the second layer is 400 μm. The relevant printing parameters are set (printing speed 15 mm / s, gas pressure 30 psi, three-dimensional array linear electrode length 140 mm, array line spacing 1.4 mm, printing needle lifting height 0.75 mm), and the second layer electrode body is printed on the top of the first layer.

[0104] Place the printed thick electrode in a vacuum oven and set the drying temperature to 70°C and the drying time to 12 hours.

[0105] In this comparative example, the width of the electrode body of the first layer and the second layer is about 400 μm, and the overall height is about 780 μm.

[0106] The schematic diagram of lithium ion half-cell assembly in this comparative example is shown in Figure 2 , the assembly method refers to Example 3.

[0107] It can be seen from the rate performance test diagram of Example 4 and Comparative Example 1 that at low charge and discharge rates such as 0.5C-1C, the specific capacity of the gradient porous thick electrode and the thick electrode without pores is about 160mAh / g, which is close to the theoretical specific capacity of lithium titanate, indicating that both electrodes can fully react under slow charge and discharge conditions. When the charge and discharge rate gradually increases, the specific capacity of Comparative Example 1 decays rapidly, and the specific capacities of 2C, 3C, 4C, and 5C are 80mAh / g, 40mAh / g, 20mAh / g, and 10mAh / g, respectively, which is consistent with the situation that the electrochemical reaction process of the thick electrode described in the background is hindered and the reaction is insufficient when the current is rapidly charged and discharged. In Example 4, a gradient porous structure is constructed, the specific capacities of 2C, 3C, 4C, and 5C are 120mAh / g, 80mAh / g, 40mAh / g, and 20mAh / g, respectively, and its rate performance is better than that of Comparative Example 1, showing a higher power density. From the capacity comparison chart of Example 4 and Comparative Example 1, when the shape parameters such as electrode width and height are almost the same, due to the formation of the porous structure, the capacity of Example 4 at the same volume is slightly lower than that of Comparative Example 1 under low rate charge and discharge, i.e. 0.5C-1C. However, after 2C rate, the capacity of Example 4 exceeds that of Comparative Example 1, which proves that the gradient porous structure has better performance when thick electrodes are charged and discharged at large currents.

[0108] From the cycle performance test graphs of Example 4 and Comparative Example 1, it can be seen that in the cycle test of charge and discharge at a rate of 0.5C, Comparative Example 1 has obvious capacity decay after 50 cycles, and the specific capacity has dropped from 160mAh / g to 120mAh / g. While Example 4 has a stable specific capacity of about 160mAh / g within 100 cycles, showing a more stable cycle performance.

[0109] Comparing Example 3 and Example 4, the porosity of the first layer of the porous thick electrode used in Example 3 is less than that of the second layer, while the porosity of the first layer of the porous thick electrode used in Example 4 is greater than that of the second layer, and the electrode porosity change gradients of the two embodiments are opposite. It can be seen from the rate performance diagrams of Example 3 and Example 4 that the rate performance of the two is not much different at 0.5C-1C, and after 2C, the specific capacity of Example 4 is higher than that of Example 3. This shows that the porosity of the electrode away from the side of the diaphragm, that is, the first layer, is larger, and the curvature of the electrode here is smaller, which can effectively improve the effective diffusion rate of the electrode at a higher rate, thereby promoting the transmission of ions during the charge and discharge process. This also shows that the porosity gradient distribution of Example 4 is more reasonable and effective for array linear three-dimensional thick electrodes. It can be seen from the cycle performance diagrams of Example 3 and Example 4 that both can basically maintain a stable specific capacity within 100 cycles.

[0110] In summary, the lithium ion half-cell with three-dimensional porous thick electrode with gradient porosity provided by the present invention has significantly improved electrochemical performance compared with the lithium ion half-cell based on three-dimensional array linear electrode without pore-forming agent. Although the capacity is slightly lower than that of the comparative example during low current charge and discharge, each embodiment has a higher specific capacity and more stable cycle performance, and the setting of the gradient porous structure can give full play to the utility of the porous structure without increasing the energy loss of the thick electrode.

[0111] The above embodiments are only examples for explaining the present invention, and are not intended to limit the implementation of the present invention. Any changes, improvements, substitutions, etc. made by those skilled in the art without departing from the innovative ideas of the present invention shall fall within the protection scope of the present invention.

Claims

1. A three-dimensional porous thick electrode with gradient porosity, characterized in that: The porous thick electrode is based on a current collector and is formed by stacking electrode slurry layer by layer. Each layer of the porous thick electrode has evenly distributed micron-sized pores, and the porosity of each layer of the electrode structure is different and is arranged in a gradient along a direction perpendicular to the electrode plane.

2. The three-dimensional porous thick electrode with gradient porosity according to claim 1, characterized in that: The shape of each layer structure of the thick electrode is any one of an array linear shape, a plane shape, a grid shape, a ring shape and a forked finger shape.

3. The three-dimensional porous thick electrode with gradient porosity according to claim 2, characterized in that: The thick electrode has a specific layer structure, the height and width of each layer structure range from 0.2 mm to 0.85 mm, the height and width are the same or different, and the width of the upper layer structure is not greater than the width of the lower layer structure.

4. The three-dimensional porous thick electrode with gradient porosity according to claim 1, characterized in that: The porosity of each layer structure of the thick electrode is between 20% and 75%, and the maximum pore size range is between 0.1 μm and 10 μm.

5. The three-dimensional porous thick electrode with gradient porosity according to claim 4, characterized in that: The porosity of each layer structure of the thick electrode is arranged in a positive gradient or a negative gradient from the current collector side to the diaphragm side, and the porosity of two adjacent layers of the structure varies in the range of 10%-275%.

6. A method for preparing a three-dimensional porous thick electrode with gradient porosity according to any one of claims 1 to 5, characterized in that: The steps include: (1) using a water-soluble salt as a pore-forming agent, mixing different amounts of water-soluble salt with an electrode active material, a conductive agent, and a binder in a solvent of N-methylpyrrolidone to prepare different groups of electrode slurries; (2) using ink direct writing 3D printing technology to deposit different groups of electrode slurries layer by layer on the current collector and form them after drying; (3) The formed electrode is immersed in deionized water to remove the pore-forming agent and then dried again.

7. The preparation method according to claim 6, characterized in that: The water-soluble salt is any one or any combination of two of sodium chloride, sodium carbonate, sodium bicarbonate, ammonium bicarbonate, sodium citrate, and sucrose; The mass of the water-soluble salt is 10-200% of the mass of the electrode active material; The electrode active material is selected from at least one of lithium titanate, lithium manganate, lithium iron phosphate, lithium iron silicate, lithium manganese silicate, lithium nickel cobalt manganese, lithium nickel cobalt oxide, sodium iron phosphate, sodium vanadium phosphate, sodium iron sulfate, sodium nickel iron manganate, Prussian white, and hard carbon; The conductive agent is selected from at least one of carbon black, acetylene black, graphene, carbon fiber, and carbon nanotubes; The binder is selected from at least one of polytetrafluoroethylene, low-pressure polyethylene, polyvinylidene fluoride and polyvinyl alcohol; The added amounts of the electrode active material, the conductive agent and the binder satisfy: 70-90 parts of the electrode active material, 10-200 parts of the pore-forming agent, 10-20 parts of the conductive agent and 10-20 parts of the binder.

8. The preparation method according to claim 6, characterized in that: The current collector is made of foam metal material, including one of foam nickel and foam copper; the thickness of the current collector is 0.1 mm-0.5 mm.

9. The preparation method according to claim 6, characterized in that: During ink direct writing 3D printing, different groups of electrode slurries are printed layer by layer from the current collector side to the diaphragm side in a positive or negative gradient according to the mass of water-soluble salt. The mass of water-soluble salt of the electrode slurry used in two adjacent layers varies in the range of 50-400%.

10. Use of the three-dimensional porous thick electrode with gradient porosity as claimed in any one of claims 1 to 5 in positive and negative electrodes of lithium and sodium ion batteries.

Citation Information

Patent Citations

  • Lithium ion battery negative electrode, preparation method thereof, lithium ion battery and battery module

    CN112216818A

  • Thick electrode, preparation method and application thereof and system device for preparing thick electrode

    CN112670443A

  • Structured electrode and preparation method and application thereof

    CN116799136A